Perancangan Kids Wear Inspirasi Karakter Tokoh Dalam Film Inside Out 1 - Putri Aprillia Sari Endah; Wuri Handayani; Naufal Arafah (VisArt: Jurnal Seni Rupa dan Design, 2026)
The limited availability of children’s fashion designs that are able to integrate emotional psychology and learning values in an integrated manner became the background of this research. This research aims to produce a children’s wear collection that represents the characters and emotional expressions of the characters in the film Inside Out 1 through a communicative, expressive, and child-appropriate design approach. The novelty of the research lies in the visualization of emotional characters into expressive and educational kids wear designs. The method used is the threestage design process by Labar & Sokolowski which includes problem definition & research, creative exploration, and implementation through character analysis, as well as the exploration of color, shape, proportion, and texture. The results of the research produced six kids wear designs representing emotional characters and one combination design displaying emotional harmonization. The research concludes that the visualization of emotional characters can be effectively applied in children’s fashion design, resulting in visually attractive designs and having educational value in introducing emotions to children. The results of this research are expected to become a reference for the development of children’s fashion design based on emotional education